Performance-Based Budgeting in the Public Sector
XX, 274 p. 10 illus., 3 illus. in color.
Keywords: This book provides a comparative analysis of performance budgeting and financing implementation, and examines failures and successes across both developed and developing countries. Beginning with a review of theoretical research on performance budgeting and financing, the book synthesises the numerous studies on the subject. The book describes the situation in the US, Australia, New Zealand, Germany, Austria and Switzerland, Netherlands and Italy, as well as in seven developing countries - Bulgaria, Czech Republic, Slovakia, Slovenia, Ukraine, Russia and South Africa, at the national, and at the local level. Each chapter provides historical and descriptive details of successful or failed experiments in performance budgeting and performance financing. Michiel S. de Vries is Chair in Public Administration at Radboud University of Nijmegen, the Netherlands. He is past president of IASIA, full member of the Group of Independent Experts on the European Charter of Local Self - Government of the Council of Europe, and member of the editorial board of numerous journals on Public Administration. His research concentrates on local government, policy evaluation, policy change and comparative public administration. Juraj Nemec is Professor of Public Finance and Public Management at Masaryk University in Brno, Czech Republic. He is the President of the Network of Institutes and Schools of Public Administration in Central and Eastern Europe (NISPAcee), Vice-President of the International Association of Schools and Institutes of Administration, and the project director of the IASIA permanent working group. David Špaček is Associate Professor at the Department of Public Economics, Faculty of Economics and Administration, Masaryk University, Brno. His primary research interests are in public administration and management, with a focus on performance management, quality management, strategic management, e-government/e-governance and human resources management.